Development of Fine Motor Skills and Language in Infants Aged 6-12 Months at Puskesmas Karuwisi, Makassar City - Sriyanah, Nour; Pawenrusi, Esse Puji; Efendi, Suradi; Pratiwi, Dewi Sari; Yati, Mimi (Universitas Aisyah Pringsewu, 2023)
Infants are the age of newborns up to one year, who go through a process of development and growth. This process passes quickly, briefly, and cannot be repeated, so it is called the